Zoonotic diseases and the COVID-19 pandemic: Economic impacts on Somaliland’s livestock exports to Saudi Arabia - Mtimet, Nadhem; Wanyoike, Francis N.; Rich, Karl M.; Baltenweck, Isabelle (Elsevier, 2021)
The livestock sector plays an important socioeconomic role in the Somaliland economy, particularly through revenues from exports. The partial ban on livestock imports from Somalia imposed by Saudi Arabia due to animal health concerns has resulted in significant negative economic impacts for the government and the value chain actors involved. In previous years, the ban was lifted during the Hajj season to meet the increased demand for sheep and goats. However, given the current COVID-19 pandemic, the Saudi government decided to suspend Umrah visits in 2020 and only allowed a very restricted number of persons to attend the Hajj pilgrimage, thus obviating the need for livestock imports. This study quantified the economic losses associated the current partial livestock ban (started in November 2016) on Somali imports and the added impacts associated with COVID. We estimate that the cumulative losses for the Somaliland livestock sector and the government are US$ 770 million over a five-year period. The additional losses imposed by the COVID pandemic, which restricted participation during the Hajj season, were estimated at US$ 42 million. Livestock producers, who are mainly pastoralists, are the most affected stakeholder group, incurring around 54% of the total losses. Our study highlights the multifaceted, and often overlooked, socio-economic and socio-cultural impacts faced by the livestock sector and general economy in the wake of public health restrictions.